Tombs of Anak - Peretti, Frank E. (Wheaton, Ill. Crossway, 1990)
The Coopers rely on their Christian faith as they search for their father's co-worker, who has disappeared in the cave-tombs of Anak
74813
Keywords: Kings and rulers; Tombs; Archaeologists